Oral candidal carriage in asymptomatic patients. (June 2016) - Mun, MSS; Yap, T; Alnuaimi, AD; Adams, GG; McCullough, MJ
Abstract: Background: Interest in the association between oral cancer risk and Candida ‐associated promotion of mucosal dysplasia continues. However, little is known of the presence and amount of oral yeast in the mouths of healthy patients without mucosal lesions. The purpose of this prospective cross‐sectional clinical study was to ascertain the prevalence and degree of carriage of Candida in the oral cavities of a non‐cancer population, with reference to a range of parameters affecting the oral environment. Methods: Oral rinse samples were collected from a sample of 203 patients attending the Royal Dental Hospital of Melbourne and analysed for the presence and degree of colonization of yeast species that were phenotypically identified as albicans and non‐ albicans species. Results: Oral yeast carriage was found in 98/203 patients (48.3%), and of these, 83 (84.7%) patients carried C . albicans . There was no statistical difference in carriage when comparing gender, age, or presence of a removable prosthesis. Conclusions: Both smoking and the presence of active carious lesions were found to be positively correlated with the carriage of oral Candida . Individuals who are current smokers are nearly seven times more likely to have oral Candida, and participants with high candidal colonization are more likely to be current smokers. Participants with active carious lesions were also more likely to carry oral Candida .